PATHOGENETICAL MECHANISMS OF IRON DEFICIENCY DEVELOPMENT IN PEOPLE WITH CHRONIC GASTRITIS TYPE B - Zelenaya, I.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Level of ascorbic acid (AA) in gastric juice and its correlation with main indicators of iron metabolism was investigated in 80 people with chronic gastritis type B. Serum ferritin was selected as the principal marker of iron metabolism. Result: the level of AA in gastric juice was significantly lower in people infected with H.pylori. Correlation between level of AA in gastric juice and serum ferritin was straight and strong. Decrease of AA concentration in gastric juice in people with chronic gastritis type B and iron deficiency, may signify that helicobacteriosis reduce antioxidant potential of gastric juice and it may be one of the factors which lead to the development of iron deficiency anemia.